If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4In(2x + 3) = 11 Reorder the terms: 4nI(3 + 2x) = 11 (3 * 4nI + 2x * 4nI) = 11 (12nI + 8nxI) = 11 Solving 12nI + 8nxI = 11 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Reorder the terms: -11 + 12nI + 8nxI = 11 + -11 Combine like terms: 11 + -11 = 0 -11 + 12nI + 8nxI = 0 The solution to this equation could not be determined.
| .15x+x=97.75 | | 4m+m=-90 | | (x+12)(x-7)=0 | | [8x]=28 | | .25(x+4)=41 | | 7/6=x/5 | | (7/28)=(3/x) | | 3x+24=4-10 | | 3(a+1)=5(a-1) | | x^3-2x^2-09+18=0 | | -112/16 | | 5x(3x-5)(x+1)=0 | | y=e^2x+17 | | Y=2x+a | | (9a-3)/3 | | Bj+m=j | | 16[x-3]=-80 | | 3d+2=12 | | X*.0147=(X-67) | | 11=3u-13 | | 11=3u+13 | | (x-67)=x*1.47 | | 6d+(5.5)=2d-(6.5) | | 6d+5.5=2d-(6.5) | | 6d+5.5=2d-6.5 | | 17x+3=17x | | -33*1/5 | | 288/6 | | (3/4)-(9/12) | | 68(x-3)=-2x+35.6 | | 10x+5y+15z= | | (x-1)(x+5)-(x+2)(x-3)=3(1+5x) |